Insights into Antimicrobial and Anti-Inflammatory Applications of Plant Bioactive Compounds - Gregoria Mitropoulou; Elisavet Stavropoulou; Natalia Vaou; Zacharias Tsakris; Chrysa Voidarou; Arsenis Tsiotsias; Christina Tsigalou; Birce Mercanoglou Taban; Yiannis Kourkoutas; Eugenia Bezirtzoglou (Microorganisms, 2023)
Plants have long been thought to contribute to health promotion due to their fiber and phenolic content, as well as their inherent biological potential. The bioactive derivatives of medicinal plants are a valuable resource in the fight against serious diseases all around the world. The present review focuses on the current state of knowledge on the usage and medicinal applications of plant bioactives. Issues concerning the effect of aromatic plant derivatives on human gut microbiota and their antimicrobial and anti-inflammatory potentials are discussed and worth further exploring.